Merchants and muleteers: infrastructure, identity, and inequality in the 18th century Andes - Ballance, Matthew, author; Van Buren, Mary, advisor; Henry, Edward, committee member; Carlyon, Jonathan, committee member (Colorado State University. Libraries, 2021)
In this thesis, I examine the way that infrastructure helped structure inequality in the 18th century Andes through the production of qualitatively different experiences of movement. Using a combination of historical, geospatial, and archaeological methods, I argue that an individual's experience of movement and lodging along the road system was mediated by their position in a hierarchy of labor. This hierarchy was principally divided between business travelers and muleteers, two positions that emerged from an 18th century economic context in which those who did the labor of physically moving goods were increasingly separated from those who owned those goods. El Lazarillo de Ciegos Caminantes is used as a historical source through which to view an elite understanding of labor identity and its relationship to infrastructure. This historic document is then analyzed using GIS techniques in order to see spatial relationships between infrastructure and class associated patterns of movement. Archaeological data is used to reveal alternative systems of infrastructure that supported the movement of labor. Ultimately, I argue that the disconnect between textual and material sources of information sheds light on both the biases of 18th century authors, as well as the persistence of Andean pastoral traditions even in a context of shifting labor dynamics.
Keywords: Camino Real; La Plata; posta; caravan; Andes; mule